Evaluation of Morphological Traits and Essential Oil Constituents Diversity in Different Populations of Achillea santolinoides subsp. wilhelmsii (K. Koch) Greuter in Hamedan Province - Mahtab Salehi; Ramezan Kalvandi; Foroozan Salehi (Majallah-i ̒Ulum-i Bāghbānī, 2024)
IntroductionThe medicinal plants have been used in traditional medicine for a long time all over the world. Over 80% of the world population depends on herbal medicines and products for healthy living, and also, a large part of pharmaceutical materials are derived directly or indirectly from plant sources. According to the new approach to the use of medicines and herbal products, the investigation of the medicinal properties of endemic plants in each region, is of particular importance. Morphological and phytochemical traits of medicinal plants are affected by the different environmental conditions as well as genetic variations. Therefore, investigating the changes in morphological and phytochemical traits of different populations of these plants in various regions and identifying the amount and constituents of their essential oils, can be effective for creating a suitable field for their planting or breeding, as well as standardizing their derived medicine products. The Achillea genus, a medicinal plant belonging to the Asteraceae family, is highly diverse in terms of morphological characteristics and essential oil constituents. 19 species of herbaceous and aromatic plants of this genus have been identified in Iran, of which 7 species are endemic. Some of the Achillea species have therapeutic properties such as reducing blood pressure and lipids, sedative, antispasmodic, analgesic, wounds treatment, antiseptic properties, treatment of stomach pain and diarrhea, stopping bleeding, etc. Materials and MethodsThis study was conducted in May 2022 in order to evaluate the diversity of morphological traits and essential oil constituents of A. santolinoides subsp. wilhelmsii (K. Koch) Greuter populations in 11 regions of Hamedan province. The plant samples were collected in the flowering stage and after measuring some morphological traits (plant height, number of flowering stem, stem diameter, inflorescence diameter, fresh and dry weight of plant, number of inflorescence, number of leaf, etc.), they were dried in shade condition. In order to investigate the physical and chemical properties of soil, soil samples were collected from a depth of 30 cm. and were transferred to the soil laboratory. The essential oils were extracted using hydro-distillation method which lasted for 4 hours. Then they were analyzed by GC and GC/MS in the Institute of Medicinal Plants in Karaj. Gas chromatography was carried out on Agilent 6890. The grouping of populations based on morphological traits and essential oil constituents, was done by cluster analysis in SPSS using the Ward method. Also, the traits correlation (quantitative) was done using the Pearson method. Results and DiscussionThe results indicated that the Vahnan population exhibited the tallest plant height at 23.20 cm, a significant difference compared to other populations. Conversely, the Nazool population displayed the lowest plant height at 13.60 cm. Regarding stem diameter, the Yalfan population showed the greatest diameter at 2.50 mm, a measure not significantly different from the populations of Islamabad, Nazool, and Varayeneh. In contrast, the Koohani population had the smallest stem diameter at 1.52 mm. The highest inflorescence diameter (4.30 cm) belonged to the Islamabad population, which statistically had no significant difference with the populations of Koohani, Vahnan and Yekan Abad, and the lowest (2.30 cm) was observed in Joorab population. The Vahnan population had the highest number of inflorescence (6.20), which statistically had no significant difference with Islam Abad, Zanganeh, Koohani, Yekan Abad and Nazool populations, and the lowest was related to the Yalfan population (3.40). The maximum leaf length was related to Varayeneh population (3 cm), which was statistically not significantly different from Yalfan, Islam Abad and Vahnan populations, and the lowest was related to Naseh Abad population (1.70 cm). Varayeneh and Yekan Abad populations respectively had the largest leaf width (4 mm and 3.80 mm) and the lowest leaf width (2 mm) was observed in the Joorab population. The highest number of flowering stems (13.80) and the maximum number of leaves (168) were belonged to Nazool population, and the lowest number of flowering stems (3.80) was related to Naseh Abad population and the lowest number of leaves (61) was related to Koohani population. Regarding the fresh and dry weight of the plant, the highest values of these traits (3.92 and 2.24 gr, respectively) was related to the Yalfan population and the lowest (1.60 and 0.79 gr, respectively) was related to the Naseh Abad population. Analysis of the essential oils chemical compositions using GC-MS, showed 28 compounds. Camphor, Fragranol, a-pinene, 1,8-cineole and Sabinene were the main constituents of the essential oil. The essential oils yield varied from 0.3 to 0.6% which the highest was related to Varayenh and Nazool populations (0.6%) and the lowest belonged to Heydareh Bala Shahr population (0.3%). Also, Islam Abad population (with the highest altitude), had the highest percentage of fragranol (43.29%). This indicates that environmental factors similar to genetic factors are effective in creating diversity in morphological and phytochemical characteristics of this plant. ConclusionIdentifying the compounds in the Iranian native plants, can provide a suitable field for the practical use of its plant resources and may be the basis of breeding programs. The various studies conducted on different species and populations of Achillea genus, have mentioned the valuable use of their extracts and essential oils in various fields such as pharmaceutical industries (in order to standardizing medicinal products), food, health cosmetics, making insecticides, etc. Researchers who have studied the essential oils of different populations of Achillea species in many regions of Iran, have emphasized on the significant difference between type and amount of the essential oil constituents. In this study, compounds such as Camphor, Fragranol, a-pinene, 1,8-cineole and Sabinene were the main components of the populations essential oils. Since fragranol is used in manufacturing the insecticides and pheromones, Islam Abad population can be used in this industry due to having high fragranol (43.29%). Also, due to the high amount of camphor in the essential oils of most of the studied populations and many uses of this compound, it can be used as an important economic resource in the health-cosmetics and pharmaceutical industries to make various creams and ointments.